Identitas Perempuan Banjar dalam Lirik Lagu Daerah Kalimantan Selatan: Analisis Semiotika Triadik Charles Sanders Peirce - Kamariah, Kamariah; Normalasarie, Normalasarie; Rahmani, Rahmani; Arifin, Johan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This research aims to reveal the construction of Banjar women's identity through Charles Sanders Peirce's triadic semiotic analysis of three South Kalimantan folk songs: Paris Barantai, Ampat Si Ampat Lima, and Saputangan Babuncu Ampat. These three songs were chosen because they contain cultural symbols that reflect the roles, emotions, and social values attached to women in Banjar society. This research uses a qualitative method with a descriptive approach, which aims to describe systematically and holistically the symbolic meaning in the context of local culture. Data collection techniques were conducted through documentation of song lyrics, literature study, and interviews with Banjar community leaders and cultural experts who fulfil certain criteria, such as mastering the Banjar language and being active in the Banjar cultural environment. Data in the form of song lyric excerpts were analysed using Peirce's triadic semiotic framework which includes the representamen (sign), object (referred meaning) and interpretant (captured meaning). The analysis was conducted through the stages of data reduction, lyric transcription, identification of lexical symbols, and interpretation of the meaning of icons, indices, and symbols based on Banjar cultural conventions and insights. The results show that women in Banjar folk songs are represented as noble, empowered, and at the centre of the cultural value system. Folk songs do not only function as entertainment, but also as a means of passing on gender values, preserving traditions, and strengthening local identity. This research reinforces the importance of oral culture as a medium in understanding the dynamics of women's identity and social values in traditional societies